2019
DOI: 10.3899/jrheum.181375
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine Ocular Toxicity: Lessons Learned

Abstract: identified case reports with 3 or fewer patients are exempt from formal review by the University of the Incarnate Word Institutional Review Board (UIW IRB) and do not require informed consent although the patient provided verbal consent. This case report satisfied ethical requirements for submission in accord with the UIW IRB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The presence of DISH is associated with older age, male sex, obesity, hypertension, and diabetes mellitus [2,23]. Toyoda et al reported a prevalence of 26%, which increased to 48% in patients over 70 years old [24].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of DISH is associated with older age, male sex, obesity, hypertension, and diabetes mellitus [2,23]. Toyoda et al reported a prevalence of 26%, which increased to 48% in patients over 70 years old [24].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, detrimental effects for skeletal muscle have been reported after two months of intraperitoneal injection of 10 mg/kg CQ five times per week [58] or after two months of daily subcutaneous injection of 15 mg/kg CQ [59]. HCQ administered at high concentration and too high frequency, induce retinopathy, cardiomyopathy, neuromyopathy and myopathy [42,60]. Searching for a compromise between ethical acceptance in terms of injections number and toxicity of the drug was finally unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CQ and HCQ are recommended as autophagy inhibitors for the autophagy flux measurement in vitro [8,56,57]. However, doses used and schedule applied should be carefully selected because CQ and to a lesser extent, HCQ, are toxic compounds able to produce vacuolar myopathy [58,59], retinopathy [60], cardiomyopathy and neuromyopathy [42]. As a lysosomotropic drug such as CQ, HCQ allows LC3-II and SQSTM1/p62 to accumulate as a probable result of lysosome deprotonation and/or inhibition of the fusion between lysosome and autophagosome, and the subsequent impairment of autolysosomal degradation [50].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of the ocular manifestation of SLE is usually targeted at reducing ocular tissue damage with the general treatment focusing on the remission of end-organ damage, improving the outcome of the disease in the long run and improving quality of life [148] In SLE, the treatment is deemed effective if the patient has a remission with an SLEDAI score less than 3. Conventionally, SLE is treated with antimalarial drugs, the commonly used one being hydroxychloroquine [194,195]. Long-term hydroxychloroquine may, however, dispose users to retinopathies [196][197][198].…”
Section: Management and Treatmentmentioning
confidence: 99%